Penentuan Kriteria Vendor Teknologi Informasi Strategis Menggunakan Metode Fuzzy Analytical Hierarchy Process: Studi Kasus PT ABC - Ardyani, Silvia Ayu; Shihab, Muhammad Rifki (The Indonesian Journal of Computer Science, 2024)
PT ABC is a national scale financial company whose services have spread throughout Indonesia and several countries in the world. Apart from that, PT ABC also encourages digitalization in improving its digital services. In improving its digital services, PT ABC involves all internal resources and IT vendors. During 2023, there will be 189 IT vendors collaborating with PT ABC. With a large number of IT vendors, it is necessary to group IT vendors to make it easier for companies to determine future strategies. Currently it is felt that determining the criteria for strategic IT vendors is no longer appropriate to the company’s conditions, so updated are needed. Determination of the criteria and subcriteria for this research was carried out through focus group discussion with 3 respondents. The results of the FGD stated 3 criteria and 2 subcriteria that could be used in this research. These criteria and subcriteria were then weighted using the fuzzy analytical hierarchy process (FAHP) method which was then tested on 25 IT vendors randomly.